(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There were various organizations and leaders which brought notable social and religious reforms in pre-independence era. Raja Ram Mohan Ray, Debendranath Tagore, Keshab Chandra Sen, Iswar Chandra Vidyasagar, Sri Ramakrishna Paramhamsa, Swami Vivekananda, Swami Dayanand Saraswati, Jyotirao Govindrao Phule etc. were the great Indian Social reformers. They brought reforms in the education fields also. The Arya Smaj was such an movement started by Swami Dayanand Saraswati. It was propounded in Bombay. It has influenced all over India especially north India. It achieved a resurgence of Vedic esteems blasting religious and social shades of malice going from worshipful admiration, superstition, unbending nature of station and untouchability to polygamy, youngster marriage, abuse of dowagers, custom of Parda, and general imbalance between the genders. In the present paper, an attempt has been made to study of the role of Arya Samaj in Haryana.